(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
A kinetic method for the accurate and sensitive determination of telithromycin has been described. The method is based on the oxidation of telithromycin with alkaline KMnO4. At a fixed time of 24 min. the formed magnate ion is spectrophotometrically measured at 610 nm. The concentration of telithromycin is calculated using the calibration equation for the fixed time and initial rate methods. Beer´s law was obeyed from 3.24-12.9µg ml-1 The assays limits of detection were 0.2-0.70µg ml-1 and the R.S.D. (n= 5) was 0.6 %. Recovery was 99.8 and 100.83%. The analytical performance of the, in terms of accuracy and precision, were statistically validated, the results were satisfactory RSD ≤ 2%. The method has been applied successfully to commercial tablet dosage form. Statistical comparison of the result with the reference method showed excellent agreement and proved that no significant difference in the accuracy and precision.